A Biblioshiny Application Using R on Zakat Index - Irni Nuraini; Thuba Jazil (SMART Insight, 2023)
This study aims to examine research patterns concerning the published zakat index. The studied data came from the Scopus database, which was accessed in its entirety on 13 February 2023. A total of 51 papers were retrieved. The data were analyzed with the Rstudio Bibliometrix program and biblioshiny instruments to determine the research advancements on the Zakat Index. The data demonstrates that the development of zakat index research began in 1994 and has accelerated since 2008. Al-Homaidi, E.A., is the most prolific writer on this subject. Zakat is the most commonly occurring keyword. Malaysia has the highest number of publications and citations on this topic. Malaysia's University Teknologi Mara has the most author affiliations. According to the themes in the zakat index study that has the potential to be expanded, this research has a great deal of room for growth.